Molecular Therapeutic Strategies Targeting Duchenne Muscular Dystrophy - Mendell, Jerry R. (2010)
Since discovery of the gene for Duchenne muscular dystrophy more than 20 years ago, scientists have worked to apply molecular principles for restoration of the dystrophin protein and correction of the underlying physiologic defect that predisposes muscle fibers to injury. Recent studies provide realistic hope that molecular therapies may help patients who have this disorder. At present only corticosteroids can improve walking ability and increase quality of life for boys with this disease. The results are modest and encumbered by side effects. We review 3 molecular therapeutic approaches that have been introduced into the clinic: (1) gene replacement therapy, (2) mutation suppression, and (3) exon skipping.